166k views
10 votes
Convert from vertex form to standard form. (3 pts). f(x) =(x-3)squared + 6

1 Answer

2 votes

Answer:

Standard form of
f(x) =(x-3)^2 + 6 is
\mathbf{x^2-6x+15}

Explanation:

Convert from vertex form to standard form
f(x) =(x-3)^2 + 6

If the vertex form is:
a(x-h)^2+k

The Standard form is:
ax^2+bx+c

Now, converting
f(x) =(x-3)^2 + 6 into standard form

We know that:
(a-b)^2=a^2-2ab+b^2

Using the formula:


f(x) =(x-3)^2 + 6\\f(x)=x^2-2(x)(3)+9+6\\f(x)=x^2-6x+15

So, Standard form of
f(x) =(x-3)^2 + 6 is
\mathbf{x^2-6x+15}

User Henry Gibson
by
4.2k points